Орнаментальні форми кримськотатарського традиційного мистецтва - Бавбекова, І. (Народна творчість та етнографія, 2005)
Historically Crimea was the land of culture of various tribes. And it had its influence on the Art style. The study of Crimea-Tatar Ornament dates to the 1880th. Its elements creates the system of symbols which gives the possibility to see the genetic ties of Crimea-Tatars with others ethnos. The author analyzed types of ornaments and their symbolic meanings.